The Environmental Practices of Dayak Local Tradition in Kapuas Hulu District - Suprianto, Bibi; Bakri, Zulfikarni (POROS ONIM: Jurnal Sosial Keagamaan, 2023)
This paper will describe the customary life practices of the Dayak indigenous community located in Kapuas Hulu Regency, West Kalimantan. This paper focuses on traditions carried out by the Dayak Tribe such as the Bapegela' ritual, and Mali Umay which has a relationship between ancestors and customary forests, as well as traditional activities carried out by the local community. This research uses qualitative research with a media and library research approach. The first research result is about the Bapegela ritual performed by the Kantuk Dayak tribe in asking Jubata for help in weighing a problem. The second is through the Mali Umay ritual which aims to preserve fields and plants in the customary forest in order to have a relationship with the ancestors of the Dayak Iban tribe. These indigenous practices create a relationship between Jubata in the preservation of their customary forests.